Mechanical, thermal and microstructural characteristics of cellulose fibre reinforced epoxy/organoclay nanocomposites - Alamri, Hatem; Low, It Meng; Alothman, Z. (Elsevier, 2012)
Epoxy nanocomposites reinforced with recycled cellulose fibres (RCFs) and organoclay platelets (30B) have been fabricated and investigated in terms of WAXS, TEM, mechanical properties and TGA. Results indicated that mechanical properties generally increased as a result of the addition of nanoclay into the epoxy matrix. The presence of RCF significantly enhanced flexural strength, fracture toughness, impact strength and impact toughness of the composites. However, the inclusion of 1 wt.% clay into RCF/epoxy composites considerably increased the impact strength and toughness. The presence of either nanoclay or RCF accelerated the thermal degradation of neat epoxy, but at high temperature, thermal stability was enhanced with increased char residue over neat resin. The failure micromechanisms and energy dissipative processes in these nanocomposites were discussed in terms of microstructural observations.